The Role of High-Tech Jobs in Regional Development - A. A. Ugryumova; M. V. Savelyeva (Управленческие науки)
An essential reserve of the innovative scenario of social and economic development of the regions is the creation, the improvement and the functioning of high-tech jobs (HTJ). Such jobs require clear identification and a special managerial approach for their organization. Simultaneously, these processes in the conditions of different territories need an individual approach. The purposes of the research are to identify the key characteristics of HTJ, to identify the advantages and risks of creating a large number of HTJ for the regions, to identify the main measures to create HTJ. In the study there have been used methods of analysis and synthesis of information, systematic, logical, comparative and economic analysis, expert assessments. It is important to clearly delineate both the components of HTJ and their quantitative measurement. The significance of HTJ is confirmed by their high productivity and in turn requires additional investment to create them. It is especially necessary to direct the processes for the formation of HTJ in high-tech and knowledge-based industries of the national economy, since the creation of HTJ in technologically backward sectors can lead to a low return on investment. The study of dynamics, industry specificity and forms of HTJ organization allows us to generalize positive experience in this area and develop recommendations for stimulating of organization of such jobs. The main criteria for the allocation of high-tech jobs include the use of advanced technologies; high production efficiency (labour productivity); working conditions that meet the strict modern standards; quality education and high qualification of the specialists who work at the workplace; the high wages of such employees; the significant cost of creating a new job and the integration of these jobs into key needs of the territories. These criteria are used to determine indicators and to make a quantitative or qualitative assessment. Threshold values are set for each indicator, confirming or denying the high-tech jobs. Recommendations on stimulating the organization of such jobs are developed based on a study of the dynamics and sectoral specifics of the HTJ. Among them are taking into account the qualitative and quantitative characteristics of modern HTJ; implementation of tax and investment support in connection with the sectoral focus of the processes of formation of HTJ in different regions; current and future monitoring of HTJ in order to control the situation to enhance the socio-economic development of the regions.